Predicting sustainable development goals through the industry 4.0: Insights from public listed companies - Muhammad Shabir, Shaharudin; Yuvaraj, Ganesan; Fernando, Yudi; Noor Hazlina, Ahmad; Azlan, Amran; Lee, Khai Loon (Universiti Malaysia Pahang, 2023)
In an ideal world, publicly listed companies would be forced to publish a report on the Sustainable Development Goals (SDGs). The abandonment of SDG reporting in annual reports by public corporations is the focus of this study. We noticed in recent years that many companies are unable to recognise and commit to the Sustainable Development Goals (SDGs) in their annual reports. We observed that Malaysia prioritises economic growth above environmental concerns. Malaysia's economic growth and health system have been jeopardised as a result of the current COVID-19 outbreak. It will be difficult to achieve the other sustainable development objectives if there is a significant prevalence of chronic infectious and non-infectious diseases, as well as a lack of physical, mental, and social well-being in society. In this study, a collection of primary data gathered from the Bursa Malaysia will be used for performance analysis and forecasting. The analytical tools used for this inquiry were Power BI and RapidMiner. In the first activity, we discovered that software and services businesses who use IR 4.0 had the best SDG implementation performance. According to the study, there is a significant relationship between organisations' use of IR 4.0 and their efforts to fulfil the SDGs. It will be easier to meet the Sustainable Development Goals with broad IR 4.0 adoption in a company. According to the results of the survey, Selangor is the state with the highest degree of company SDG implementation. In conclusion, predicted data reveal that states and specific SDGs have a substantial influence on corporate adoption of SDGs. Finally, Selangor-based software and service enterprises provide the most contribution to the achievement of the Sustainable Development Goals.